2010
DOI: 10.1089/fpd.2008.0223
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Serological and Molecular Methods for Diagnosis of Toxoplasmosis in Women and Small Ruminants in Egypt

Abstract: Routine serological diagnosis of toxoplasmosis provides high sensitivity, but specificity varies depending on the test used; false-positive results (IgM) have been reported. Blood samples were collected from 88 women (59 pregnant and 29 nonpregnant) and 86 contact animals (62 sheep and 24 goats) at El Fayoum Governorate during the period from October 2005 to December 2006. All collected samples were tested for Toxoplasma gondii infection by serological tests (ELISA IgM & IgG and Sabin-Feldman dye test) and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 23 publications
4
20
4
Order By: Relevance
“…These values were lower compared to 45.8% and 30.5%, respectively for specific IgG antibodies detected by the Sabin-Feldman dye test in two separate studies among pregnant women [69], however, our results were higher than 0.6% among pregnant women in Norway [70]. …”
Section: Discussioncontrasting
confidence: 93%
“…These values were lower compared to 45.8% and 30.5%, respectively for specific IgG antibodies detected by the Sabin-Feldman dye test in two separate studies among pregnant women [69], however, our results were higher than 0.6% among pregnant women in Norway [70]. …”
Section: Discussioncontrasting
confidence: 93%
“…The prevalence of IgG antibodies among pregnant women in Dakhalia governorate, Mansoura University Hospital was 44%. [1] A similar percentage (45.8%) was reported by El Fayoum Governorate [43] and Alexandria governorate (46.2%). [38] This may be attributed to the difference in diagnostic tests, sample size, characteristics of the population in each governorate and their exposure to relevant risk factors.…”
Section: Discussionsupporting
confidence: 55%
“…[1,37] In Egypt, the majority of T. gondii infection studies emphasized Lower Egypt (Dakhalia governorate), [1,12] Alexandria governorate, [38] Menoufia governorate, [39] Zagazig, [40] Tanta [41] and Qualyobia Governorate, [42] and only one discussed Upper Egypt (El Fayoum Governorate). [43] Nearly all of the previously mentioned studies that addressed toxoplasmosis emphasised diagnosis, the prevalence, and complications of infection, association between it and other health conditions and its determinant factors; while none have reported related preventive measures. Moreover, studies that assessed the pregnant women's perception regarding this opportunistic infection and state of toxoplasmosis-related anxiety level in Northern Upper Egypt don't exist, such data are needed for initiating an educational health program, thereby, helping in the control measures against congenital toxoplasmosis, especially in the absence of a routine serological screening program.…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt previous studies showed that there is high sero-prevalence for toxoplasmosis in sheep and goat (Barakat et al, 2009;Ghoneim et al, 2010). These findings correlated eating raw infected sheep and goat meat or drinking their raw milk with increased Toxoplasma infection in pregnant women.…”
Section: Discussionmentioning
confidence: 89%
“…In Egypt, several studies have been performed to detect T. gondii infection in human and animals (Elsheikha et al, 2009;Ibrahim et al, 2009;Ghoneim et al, 2010;El Deeb et al, 2012;Nassef et al, 2015). However, the data describing the role of T. gondii infection in acquiring serious adverse pregnancy outcomes as abortion, stillbirths or congenital malformation among pregnant women in Egypt is still limited (Ibrahim et al, 2009).…”
mentioning
confidence: 99%